Total Synthesis and Biological Assessment of Mandelalide A. Issue 4 (7th December 2015) - Brütsch, Tobias Michael; Bucher, Pascal; Altmann, Karl‐Heinz
Abstract: A new convergent total synthesis of the marine macrolide mandelalide A (1 ) has been developed that is based on macrocyclic ring closure by a Shiina‐type macrolactonization and the construction of the requisite precursor seco acid by a highly efficient Sonogashira cross‐coupling reaction between two fragments of comparable complexity. Key steps in the elaboration of the acid building block were the enantioselective, catalytic addition of a protected acetylene to crotonaldehyde and the construction of the tetrahydropyran unit that is embedded in the macrocycle by means of an acid‐catalyzed Prins reaction. The synthesis of the alcohol fragment features the formation of the trisubstituted tetrahydrofuran ring through an acetal cleavage/epoxide opening cascade reaction and a rarely used radical alkynylation of a primary alkyl iodide. Intriguingly, the dihydroxylation of a terminal double bond as part of the synthesis of this building block gave the same major product for both the α‐ and β‐AD‐mix reagents, albeit with moderate or low selectivity. Synthetic mandelalide A (1 ) was a potent proliferation inhibitor of A549, HT460, and H1299 human lung cancer cells in vitro, but not of SK‐ N ‐SH neuroblastoma cells. However, in no case did we observe complete cell kill even at the highest compound concentration tested (5 μm ). Abstract : Cascade reaction : Total synthesis of the marine macrolide mandelalide A (1 ) has been achieved from crotonaldehyde, ( S )‐1, 2‐ O ‐isopropylideneglycerol, andl ‐rhamnose. Final assembly of the core macrocycle of1 was based on the Sonogashira coupling of2 and3, semireduction of the triple bond, and Shiina macrolactonization as the key steps. Mandelalide (1 ) reduced the growth of human cancer cells in vitro with high potency, but did not appear to be ultimately cytotoxic.